Beyond Interreligious Dialogue: Dialogue of Life as a Means to Peaceful Co-Existence in Nigeria - Olorunnisola, Titus S. (European Scientific Journal, ESJ, 2019)
Interreligious dialogue has gained prominence in Nigeria against the backdrop of cultural and religious plurality cum tolls of violence, loss of life, vandalism, and disruption of peaceful coexistence in the nation. Huge resources have been invested into various forms of interreligious dialogue. However, interreligious dialogue has proved quasi-effective due to mistrust, dishonesty, and lack of commitment to the common goal of dialogue as a means of promoting mutuality in a religiously plural society. The cycle of killings continues unabated with its corresponding effects on political and economic situations. Hence, this paper proposes that Nigeria must shift from the promotion of interreligious dialogue to dialogue of life as a worthy alternative to promote mutuality. Drawing a line of demarcation between interreligious dialogue, which exists as a means to building bridges across religions, and dialogue of life, that perceives and focuses on life beyond the scope of religion, this paper stresses that both the government and civil society groups must arise to promote genuine dialogue of life to bring peaceful coexistence and mutuality.